First demonstration of collision avoidance and orbit control for pico-satellites — UWE-4. (August 2021) - Kramer, Alexander; Schilling, Klaus
Abstract: Despite the transfer of many typical functionalities to very small satellites, precision attitude and orbit control capabilities are still a domain of conventional large satellites. UWE-4 has now demonstrated orbit control capabilities on board of a pico-satellite for the first time. The orbit altitude of UWE-4 was raised and lowered using the electric propulsion system NanoFEEP. An early detected collision danger enabled the execution of an avoidance maneuver in July 2020 to increase the distance of closest approach. This contribution describes the UWE-4 orbit control system and the related evaluations during operations. Highlights: Electric propulsion demonstration as viable orbit control actuator on pico-satellites. Altitude change of miniaturized satellite for accelerated de-orbiting demonstrated. Collision avoidance maneuver on pico-satellite prevents low Earth orbit space debris.